DEVELOPMENT OF PBL MODEL SCIENCE E-MODULES TO IMPROVE PROBLEM-SOLVING SKILLS IN STATIC ELECTRICAL MATERIALS: Siswa Kelas Ix SMP Negeri 11 Mimika - Suprawati; Alfred Alfonso Antoh; Hotlan Samosir; Virman; Rendra Christian Samosir (Jurnal Ilmu Pendidikan Indonesia, 2026)
This study aims to develop a science e-module through the Problem Based Learning (PBL) model on Static Electricity material and test its effectiveness on the problem-solving skills (KPM) of grade IX students. The method used is Research and Development (R&D) with the ADDIE model (Branch, 2009). The research subjects were 30 students of class IX A SMP Negeri 11 Mimika. The instrument is in the form of a 11-item KPM test (Arikunto, 2010). The analysis technique used n-Gain descriptive analysis of percentages and categories on the Likert scale (Hake, 1999). The results of the study showed: (1) E-modules were declared very feasible to use with an average material feasibility of 97.68%, media feasibility of 96.72%, teacher response of 98.33%, student response of 96.39%, and the average overall feasibility of e-modules based on validator assessments of 96.80% (Ministry of National Education, 2008). (2) The e-module effectively increased KPM with an average pre-test of 38.98 to 71.98 in the post-test and n-Gain of 0.54 in the medium category. Conclusion: the PBL model science e-module is feasible and effective in improving students' problem-solving skills in Static Electricitymaterial.